Tertiary lymphoid structures are critical for cancer prognosis and therapeutic response - Zhang, Qianqian; Wu, Suhui (Frontiers in Immunology, 2023)
Tertiary lymphoid structures (TLSs) are ectopic lymphocyte aggregates that form at sites of chronic inflammation, including cancers, in non-lymphoid tissues. Although the formation of TLSs is similar to that of secondary lymphoid organs, the pathogenic factors leading to TLS formation in cancerous tissues and the mechanisms underlying the role of these structures in the intra-tumoral adaptive antitumor immune response are not fully understood. The presence of TLSs may impact patient prognosis and treatment outcomes. This review examines the current understanding of TLSs in cancers, including their composition and formation as well as their potential to predict prognosis and therapeutic efficacy, and the strategies to induce TLS formation for cancer treatment.